Chapter 4 Contracts via comics Migrant workers and Thai fishing vessel employment contracts - Ketola, Anne (Taylor & Francis, 2023)
Comic contracts are legally binding contracts presented as comics, where the parties to the contract are represented as characters and the contract terms are communicated mainly visually. This chapter examines a comic contract created in the context of the Thai fishing industry. The industry is dependent on Myanmar and Cambodian migrants for its viability, but it is also notorious for the abuse that they can suffer on the vessels. The new contract is created in a visual format to ease the language barriers between the local vessel owners and the migrant workers. In comparison to the employment contracts offered to this group of workers in the past, this particular type of contract aims to afford the employee the dignity of autonomously understanding their rights during employment. In this chapter, we examine how the creators of the comic contract have used visual resources to create a document that is comprehensible by its users and able to fulfil its function in legal knowledge exchange.